ALLAN SEKULA'S FISH STORY— VISUALIZING GLOBALIZATION, INTERTEXTUALITY, AND CRITICAL REALISM. (2nd September 2019) - Jang, Sunhee
Abstract : Allan Sekula's photobook Fish Story (1995) consists of seven chapters and includes around 100 photographs and text. Dealing with a vast range of geographical locations, Fish Story speaks to global capitalism's influences on the sea — the rise and fall of maritime industries and the circulation of laborers and capital. However, the entire fourth chapter of the photobook is dedicated to South Korea — the chapter focuses on the local city, Ulsan where the world's largest shipyard, Hyundai Heavy Industries, resides. Though the chapter, the viewers are able to make sense of how the country achieved a rapid economic growth after the Korean War (1950–1953). In this regard, I will analyze how the complicated structure of the photobook, as well as interaction between images and text work for representing the socioeconomic tensions around South Korea — the tensions between global and local, as well as migration caused through globalization. Then, I will examine how the photobook speaks to the invisible power exercise of global capitalism. Through this research, I suggest a "surface reading", an alternative to "symptomatic reading" as a way to view Sekula's critical realism.